The population of the north of the USSR - Armstrong, Terence (Polar Record, 1962)
With the release of somewhat fuller information on the results of the Soviet census of January 1959 it is now possible to gain a more complete picture of the population of the northern parts of the USSR. Figures are available for major administrative areas down to the level of oblast ' and natsional'nyy okrug , for all towns of over 50,000 inhabitants and for certain smaller ones. There is, however, no generally agreed definition on the extent of “the north”, and, furthermore, none of the definitions which are used for specific cases (e.g. labour law, building regulations) follow the boundaries of major administrative areas. It is possible, therefore, to obtain an accurate figure only for an arbitrary definition of the north, in the case when its southern limit coincides with major administrative boundaries. But rough approximations are now available for certain areas defined as “the north”, and it is also possible to make a more accurate guess than before of the population within the boundaries of some of the other defined areas.